Mathematical models for evaluation of operational readiness of periodically inspected electronic systems - Ulansky, V.V.; Machalin, I.A. (Математичні машини і системи, 2012)
The mathematical models and theorems that identify stationary and non-stationary coefficients of operational readiness are developed for an arbitrary and exponential distribution of time to failure of avionics systems. Proven expressions, in contrast to all other known, take into account the trustworthiness characteristics of multiple inspections. It is shown that the mean time between unscheduled repairs of the system is largely determined by the probability of a false failure.